2015
DOI: 10.1073/pnas.1501676112
|View full text |Cite
|
Sign up to set email alerts
|

Minimal genomes of mycoplasma-related endobacteria are plastic and contain host-derived genes for sustained life within Glomeromycota

Abstract: Arbuscular mycorrhizal fungi (AMF, Glomeromycota) colonize roots of the majority of terrestrial plants. They provide essential minerals to their plant hosts and receive photosynthates in return. All major lineages of AMF harbor endobacteria classified as Mollicutes, and known as mycoplasma-related endobacteria (MRE). Except for their substantial intrahost genetic diversity and ability to transmit vertically, virtually nothing is known about the life history of these endobacteria. To understand MRE biology, we … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
112
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(120 citation statements)
references
References 47 publications
(53 reference statements)
5
112
0
Order By: Relevance
“…Among those, we detected homologs that were reported to be involved in the interaction of plant growth-promoting bacteria with host plants (Supplementary Table S3). In contrast to other, obligate endofungal bacteria that live in symbiosis with their fungal hosts, RrF4 does not have a reduced genome (Lackner et al, 2011;Ghignone et al, 2012;Fujimura et al, 2014;TorresCortĂ©s et al, 2015;Naito et al, 2015), which may indicate a facultative symbiosis of RrF4 with P. indica. The high similarity (in size and gene content) of the chromosomal genomes of RrF4 and C58 indicated that RrF4 did not lose any essential genes or partial genetic pathways.…”
Section: Resultsmentioning
confidence: 89%
“…Among those, we detected homologs that were reported to be involved in the interaction of plant growth-promoting bacteria with host plants (Supplementary Table S3). In contrast to other, obligate endofungal bacteria that live in symbiosis with their fungal hosts, RrF4 does not have a reduced genome (Lackner et al, 2011;Ghignone et al, 2012;Fujimura et al, 2014;TorresCortĂ©s et al, 2015;Naito et al, 2015), which may indicate a facultative symbiosis of RrF4 with P. indica. The high similarity (in size and gene content) of the chromosomal genomes of RrF4 and C58 indicated that RrF4 did not lose any essential genes or partial genetic pathways.…”
Section: Resultsmentioning
confidence: 89%
“…However, many plant-associated microbes remain undescribed (3,4) and/or are found in association with, or as symbionts of, other microorganisms (5-14, [49][50][51][52]. One example of these microbial symbioses is that between plant-associated fungi and their bacterial endosymbionts (endobacteria, endofungal bacteria, or endohyphal bacteria [EHB]).…”
mentioning
confidence: 99%
“…These observations parallel those found in animal mitochondria (5) and angiosperm chloroplasts (6), which begs the question of how universal these evolutionary trends are among heritable endosymbionts. In PNAS two companion articles (7,8) provide a first glimpse of the endosymbiont genomes from a group of ancient and diverse fungi.…”
mentioning
confidence: 99%
“…Most AMF harbor heritable endosymbionts named Mollicutes-related endobacteria (MRE) (11), which have unknown biological roles. To infer the functions of MRE, the authors of these two studies (7,8) performed genome sequencing of MRE from four diverse AMF species, including Dentiscutata heterogama (Dh), Racocetra verrucosa (Rv), Claroideoglomus etunicatum (Ce), and Rhizophagus clarus (Rc) (Fig. 1 and Table 1).…”
mentioning
confidence: 99%